Interleukin-33 increases antibacterial defense by activation of inducible nitric oxide synthase in skin. - Changwei Li; Hongquan Li; Ziwei Jiang; Tian Zhang; Yue Wang; Zhiheng Li; Yelin Wu; Shizhao Ji; Shichu Xiao; Bernhard Ryffel; Katherine A Radek; Zhaofan Xia; et al. (PLoS Pathogens)
Interleukin-33 (IL-33) is associated with multiple diseases, including asthma, rheumatoid arthritis, tissue injuries and infections. Although IL-33 has been indicated to be involved in Staphylococcus aureus (S. aureus) wound infection, little is known about how IL-33 is regulated as a mechanism to increase host defense against skin bacterial infections. To explore the underlying intricate mechanism we first evaluated the expression of IL-33 in skin from S. aureus-infected human patients. Compared to normal controls, IL-33 was abundantly increased in skin of S. aureus-infected patients. We next developed a S. aureus cutaneous infection mouse model and found that IL-33 was significantly increased in dermal macrophages of infected mouse skin. The expression of IL-33 by macrophages was induced by staphylococcal peptidoglycan (PGN) and lipoteichoic acid (LTA) via activation of toll-like receptor 2(TLR2)-mitogen-activated protein kinase (MAPK)-AKT-signal transducer and activator of transcription 3(STAT3) signaling pathway as PGN and LTA failed to induce IL-33 in Tlr2-deficient peritoneal macrophages, and MAPK,AKT, STAT3 inhibitors significantly decreased PGN- or LTA-induced IL-33. IL-33, in turn, acted on macrophages to induce microbicidal nitric oxygen (NO) release. This induction was dependent on inducible nitric oxide synthase (iNOS) activation, as treatment of macrophages with an inhibitor of iNOS, aminoguanidine, significantly decreased IL-33-induced NO release. Moreover, aminoguanidine significantly blocked the capacity of IL-33 to inhibit the growth of S. aureus, and IL-33 silencing in macrophages significantly increased the survival of S. aureus in macrophages. Furthermore, the administration of IL-33-neutralizing antibody into mouse skin decreased iNOS production but increased the survival of S. aureus in skin. These findings reveal that IL-33 can promote antimicrobial capacity of dermal macrophages, thus enhancing antimicrobial defense against skin bacterial infections.